Undrained shear strength-water content relationship for sewage sludge - O'Kelly, Brendan (My University, 2013)
Micro-fibrous organic clays include sludges and residues derived from municipal and industrial treatment processes. This paper studies the relationship of water content w against remoulded undrained shear strength sur of one such material, namely sewage sludge (biosolids), and the factors affecting the coefficients a and b in the equation ___ Data for sur in fall-cone, vane shear and triaxial compression (TC) tests were examined, considering the material?s mineralogical, physiochemical and biological properties. The effects of the different shearing modes, rates and confinement pressure on the mobilised strength were studied, since the different apparatuses approach the estimation of strength in different ways. The scalar relating the deduced sur values in vane shear to TC was not singular, but was particularly sensitive to the confining pressure applied in TC tests, and also to the difference in strain rate between the different tests. The deduced sur from the miniature vane was between 1.19 and 1.40 times that mobilised in quick-undrained TC of 38 mm diameter specimens under sigma3 of 100 kPa. New methods of analysis are presented to estimate the strength contribution of the gel-like pore fluid to the mobilised sur, and also to determine more accurately the water content corresponding to the fall-cone liquid limit condition.
PUBLISHED
Keywords: Sewage